Swimming hydrodynamics: New insights about drag and propulsion and their interaction into performance - Lopes, Tiago Jorge Duarte Gonçalves (2024)
In Swimming, there are numerous factors that influence performance, where hydrodynamic effects play a key-role. Hydrodynamics in swimming include resistance forces (drag) and propulsive forces. Due to all its complexity, hydrodynamics is one of the most studied areas in swimming. Drag has been extensively studied in swimming. Therefore, the first objective was to better understand how resistive forces are measured with a focus on active drag since swimmers spend of the race swimming. There are experimental and numerical methods to measure or estimate drag. Of all the existing methods for measuring drag, there is no gold standard. Indeed, all studies that compared methods reached the same conclusion: they all measure the same phenomenon despite differences among them. This may occur due to the characteristics of each method. A secondary objective was to use an equipment that collects propulsive data and understand the relationship of propulsive force with other swimming determinants. This is an equipment that is simple to use and understand, with the possibility of being used in a training context. It consists in a wireless sensor that also provides the trajectory of the hand. This way, it was possible to understand at what point of the arm-pull swimmers generate greater forces. All this information is acquired in real time through a mobile application that transmits the swimmers' outputs. In this study, swimming speed, propulsive force and other kinematic and kinetic variables did not change significantly (p < 0.05) between sections (only the intracyclic fluctuation of swimming speed decreased significantly, p = 0.005). Realizing that swimming speed was determined by the interaction of kinematic and kinetic variables, specifically by propulsive force and active drag coefficient. The third objective was to understand and explain the relevance of using the drag coefficient in hydrodynamic studies. Seeking to improve the efficiency and performance of swimmers, allowing the identification of areas for improvement in swimming technique and the development of more effective training strategies. The drag coefficient can be calculated based on the value of force, obtained by both drag and propulsion, providing a crucial measure to understand and optimize the interaction between the swimmer and the water during swimming. It is possible to see that swimmers have a greater active drag coefficient than the passive one, but with a strong agreement between them. Greater active than passive drag can probably be due to the larger frontal surface area during active conditions. Active coefficient data appears to be a more absolute indicator of drag for determining a hydrodynamic profile. Better than studying isolated cases of propulsion or drag.